2021
DOI: 10.3390/agriengineering3010004
|View full text |Cite
|
Sign up to set email alerts
|

Design and Experimental Study of a Wine Grape Covering Soil-Cleaning Machine with Wind Blowing

Abstract: Due to the cold and dry climate during the winter season of Central Asia, in order to prevent frostbite and vines drying out for wine grapes, the common methods are burying the vines in winter under a thick layer of soil and then cleaning them out in the next spring. The design of existing vine digging machinery is not precise enough and can only remove the outer layer of the soil on both sides and the top. It cannot clean the soil from the central area of the buried vine. Sometimes, the branches and buds get … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The collision recovery coefficient reflects the ability of a colliding object to recover to the original shape [23]. Newton's collision law implies that for two objects with known materials, the recovery coefficient is defined as the ratio of the relative separating velocity between two colliding objects to the relative approaching velocity before the collision [24][25]:…”
Section: Measurement Of Collision Recovery Coefficientmentioning
confidence: 99%
“…The collision recovery coefficient reflects the ability of a colliding object to recover to the original shape [23]. Newton's collision law implies that for two objects with known materials, the recovery coefficient is defined as the ratio of the relative separating velocity between two colliding objects to the relative approaching velocity before the collision [24][25]:…”
Section: Measurement Of Collision Recovery Coefficientmentioning
confidence: 99%
“…The residual soil still needs to be removed manually. To achieve full soil cleaning effect, a wine-grape noncontact blower that can be hung on a tractor and operated while driving can use a scraper to remove 60% of the cold-proof soil and then use a blower to blow away the remaining soil (Yang et al 2021 ). However, this method will cause dust to blow across the sky in the process of operation, affecting the ecological environment and human health.…”
Section: Covering Vines With Soil To Prevent Coldmentioning
confidence: 99%
“…When studying the operation rule of the shaper for collecting soil on the ridge and analyzing the main influencing factors on the quality of collected soil on the ridge, it is found that the quality of collected soil on the ridge is not only related to the structural parameters and soil parameters of the shaper but also to the installation angle of the shaper. Suppose the angle between the working surface of the shaper and the moving direction of the machine is α (that is, the installation angle α), then the larger the installation angle α, the larger the operation width and the greater the resistance of the scraper, which is prone to cause the soil to be piled up [16][17][18]. If the installation angle α is too small, it cannot meet the required width of the seedbed, that is, the installation angle α should be reduced when the required width of the seedbed is met.…”
Section: Mechanical Analysis Of Shapermentioning
confidence: 99%